2008
DOI: 10.1371/journal.ppat.1000142
|View full text |Cite
|
Sign up to set email alerts
|

XIAP Regulates Cytosol-Specific Innate Immunity to Listeria Infection

Abstract: The inhibitor of apoptosis protein (IAP) family has been implicated in immune regulation, but the mechanisms by which IAP proteins contribute to immunity are incompletely understood. We show here that X-linked IAP (XIAP) is required for innate immune control of Listeria monocytogenes infection. Mice deficient in XIAP had a higher bacterial burden 48 h after infection than wild-type littermates, and exhibited substantially decreased survival. XIAP enhanced NF-κB activation upon L. monocytogenes infection of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 65 publications
6
101
1
1
Order By: Relevance
“…19 Interestingly, XIAP also has been shown to be critical for toll-like receptor-modulated signaling in response to infection. 20 The patient's ascending inflammation is consistent with a maladaptive response to commensal organisms. The diagnosis of IBD in a patient with a mutation in XIAP suggests a broader role for this gene in mucosal immune regulation.…”
Section: Discussionmentioning
confidence: 92%
“…19 Interestingly, XIAP also has been shown to be critical for toll-like receptor-modulated signaling in response to infection. 20 The patient's ascending inflammation is consistent with a maladaptive response to commensal organisms. The diagnosis of IBD in a patient with a mutation in XIAP suggests a broader role for this gene in mucosal immune regulation.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, the loss of XIAP may influence immune cell activation resulting in alterations in pro-inflammatory cytokine production and cell survival in murine studies [33][34][35]. Because hypersecretion of IL-18 has been reported to play important roles in the pathogenesis of HLH [36], sustained elevation of IL-18 and its marked exacerbation on HLH in patients with XIAP deficiency would be an additional possibility to explain HLH susceptibility in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that TNF-a/IL-6 production induced by TLR2, TLR3, TLR4, or TLR7/8 was normal in Xiap 2/2 BMDMs, and XIAP deficiency did not affect TLR-induced NF-kB activation in T cells and macrophages, consistent with several recent reports. 16,[20][21][22] XIAP deficiency impaired only NF-kB activating processes that are mediated by BCL10, such as those stimulated by dectin-1, TCR, EGF, or LPA (Figures 1 and 3). Our data also agree with the observations that TNF-a-triggered NF-kB activation is normal in BCL10-knockout cells 40 and that LPS-induced NF-kB activation is not affected by deficiency in CARD9, 23 the BCL10-binding partner.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Notably, Xiap 2/2 mice are sensitive to infection of Listeria monocytogenes, with impaired innate immune responses and defective activation in macrophages. 16 XIAP is also known to activate nuclear factor (NF)-kB independent of the inactivation of caspase. 12,[17][18][19] The requirement of XIAP in NF-kB activation is stimuli selective, and XIAP is involved in nonobese diabetic (NOD)2-initiated NF-kB activation but is also dispensable in tumor necrosis factor (TNF)-a-and lipopolysaccharide (LPS)-induced NF-kB activation.…”
Section: Introductionmentioning
confidence: 99%